The Hirsch Institute of Tropical Medicine Asella, Äthiopien - Häussinger, Dieter (De Gruyter, 2019)
In 2013, the Hirsch Institute of Tropical Medicine (HITM) was officially inaugurated as a branch of the Department of Gastroenterology, Hepatology, and Infectious Diseases at Heinrich Heine University Düsseldorf under the direction of Professor Dieter Häussinger. The HITM serves as a place of scientific medical knowledge transfer, postgraduate medical training, and of conducting scientific projects relating to tropical medicine and infectious diseases. The publication relates the past activities of the institute, its history, and perspectives. Moreover, it permits a look behind the scenes during the construction of the institute in Africa and describes the living conditions and impressions of the staff.